[PP.36.04] THE RELATIONSHIP BETWEEN VARIOUS METHODS OF CARDIOVASCULAR RISK ASSESSMENT AND NON-INVASIVE ENDOTHELIAL FUNCTION MEASURES. (September 2016) - Wilk, G.; Osmenda, G.; Nowak, M.; Rajch, D.; Sliwa, T.; Maciag, J.; Czesnikiewicz-Guzik, M.; Guzik, T.
Abstract : Objective: There are several clinical scoring systems for cardiovascular risk. It is however not clear how individual risk scoring systems are related to endothelial dysfunction, which is known to underlie the pathogenesis of the disease. Accordingly, we aimed to analyse the relationship between several, independent measures of vascular dysfunction and various scores of cardiovascular risk in a primary prevention population. Design and method: The group of 170 subjects, with a negative history of cardiovascular disease were examined. The mean age was 57.3 ± 6.9; 84 (49.4%) were men. Cardiovascular risk was independently estimated using the following risk scales: FRAMINGHAM 2008, SCORE, ASCVD, PROCAM and QRISK. Endothelial function was assessed by: Flow Mediated Dilation (FMD) and Nitroglycerin-Mediated Dilatation (bNMD) of the brachial artery; measurement of reactive hyperaemia using Peripheral Arterial Tonometry (RH-PAT) with Endo-PAT 2000® device and by assessment of Pulse Wave Velocity (PWV) using SphygmoCor EM3. Carotid artery Intima Media Thickness (IMT) was measured as a measure of sub-clinical atherosclerosis. Results: Classical risk score calculators were correlated with most endothelial function measures apart from RH-PAT, which was significantly related only to FRAMINGAM Score. Classical flow mediated dilatation showed greatest degree of correlation and FRAMINGHAM and SCORE appear to represent endothelial function status (Table 1). Figure. No caption available. Conclusions: Brachial FMD appears to provide greatest degree of relation to cardiovascular risk scales. FRAMINGHAM and SCORE are most related to indices of vascular function.